Identification of genetic alterations in couples and their products of conceptions from recurrent pregnancy loss in North Indian population - Srivastava, Priyanka; Bamba, Chitra; Chopra, Seema; Rohilla, Minakshi; Chaudhry, Chakshu; Kaur, Anupriya; Panigrahi, Inusha; Mandal, Kausik (Frontiers in Genetics, 2023)
Background: Recurrent pregnancy loss (RPL) is one of the most common pregnancy-related complications, which can be stressful and emotionally draining for a couple. Genetic alterations, which are responsible for RPL, can be present in either of the three genomes: mother, father, or their fetuses. In addition, environmental factors interacting with these three genomes can affect germline cells. With this aim, the present study was conducted to understand the underlying etiology of RPL using Next-generation sequencing (NGS; couple exome and TRIO exomes) in combination with cytogenetic tests [karyotyping and chromosomal microarray (CMA)]. Material & Methods: In present study we recruited 61 couples with RPL (history of ≥ 2 abortions) and 31 products of conceptions (POCs). For all couples karyotyping was done at the time of recruitment, followed by collection of POC samples and parental blood samples. Before processing POC samples for CMA, they were checked for maternal cell contamination (MCC) by QF-PCR. In POC samples with no pathogenic variant, TRIO exome sequencing was done. Further, in case of unavailability of POC sample, couple exome sequencing was done for RPL couples. Results: In six individuals out of 61 couples (5%), abnormality in karyotypes was detected. Among 116 normal karyotypes, there were 11 heteromorphisms (9.5%), for which the couples had to be counselled and reassured. Out of the 31 POCs, 10 were excluded because of MCC (around 30%) and one had major aneuploidy. CMA in POCs identified pathogenic copy number variations (CNVs) in 25% of cases (5/20) and variant of unknown significance (VUS) in 20% of cases (4/20). Autosomal trisomy was the most frequent chromosomal abnormality diagnosed. NGS was performed to establish single-gene causes of RPL. Couple exome sequencing was performed in 20 couples, and 14 were found to be carriers for autosomal recessive conditions. A total of 50 potential disease-causing variants in 40 genes were identified in 33 of 40 individuals (82.5%). Putative causative variants were identified in 37.5% of the TRIO cases (3/8). Mutations in few important genes (SRP54, ERBB4, NEB, ALMS, ALAD, MTHFR, F5, and APOE), which are involved in vital pathways, early embryonic development, and fetal demise, were identified in the POCs. Conclusion: It enhances our understanding of prenatal phenotypes of many Mendelian disorders. These mutated genes may play an auxiliary role in the development of treatment strategies for RPL. There was no correlation of the number of abortions with etiological yield of any technique to detect the cause of RPL. This study shows the utilization of combination of techniques in improving our understanding of the cause of early embryonic lethality in humans.